Representações identitárias de Feira de Santana em folhetos da literatura de cordel: a feira livre e a feira de gado - Caldas, Marly dos Santos (2010)
This paper aims to analyze identity representations of the city of Feira de Santana in the leaflets of Cordel Literature. So, it looks to travel the paths of Cordel, from its origins until the arrival of the Brazilian northeast where I find fertile ground set roots. The oral characteristics of the string, the rhythm of his verses and rhymes make this literature a significant place of identification with the artist seeks to insert him popular beliefs, dreams, daily life and cultural expressions of its people. Furthermore, we did a search on Feira de Santana, sourcing, training and representative elements of their culture. Are important for this work the building blocks of aspects of city's cultural identity. Around this farm, there was a fair free trade mainly for cattle that grew and transformed the farm into a city that now has nearly six hundred thousand inhabitants. Flyers bring Cordel literature as the main theme of the cultural elements that acted for the construction of the city, like the street fair, a cattle fair and the cowboy. Researching a universe of nearly forty leaflets highlight twenty-two presenting the topic. Of these, four chose to be our main corpus of study. Other searches were made in order to achieve our goal: we start from an analysis of culture, popular culture and oral tradition, with the rich contribution of Paul Zumthor, Stuart Hall, Clifford Geertz and others, we seek scholars string as the Idelette Muzart-Fonseca Santos, Cascudo, Diegues Jr., and others who study this issue and proceeded to find the research done on Feira de Santana, whose main texts were Rollie Poppino, Eurico Alves Bonaventure, Moreira Vicente Diocletian addition to articles, essays and reviews published by magazines and Sitientibus league and a half of Uefs. Finally, we analyzed the leaflets to fulfilling our goal.